Antimicrobial and antioxidant active packaging incorporated with hop (Humulus lupulus L.) extract: development, characterization and application in meat product - Arruda, Tarsila Rodrigues (2024)
The search for alternatives to fossil-based plastics has grown abruptly in recent years, leading to the investigation of biopolymers as possible substitutes and, in special, polylactic acid (PLA) has shown good prospects in many industrial areas. In parallel, active packaging using biopolymers has gained interest as an ally to the food sector, potentially decreasing food losses. In this sense, the present study aimed to develop and characterize active antimicrobial and antioxidant food packaging based on PLA and natural bioactives from hop (Humulus lupulus L.). To provide a better understanding of the natural bioactives and their technological aspects, including complexation with cyclodextrins, prospects in active packaging development boosted to elaborate a comprehensive review in Chapter Article 1. Chapter Article 2, a commercial β- acids-rich hop extract was directly incorporated in different concentrations (0.1-5% w/w) into PLA-based sheets. Mechanical and thermal findings indicated that possibly the different fractions of the extract logged into distinct sites in the polymeric matrix, with the potassium salts of β-acids located majorly inside the PLA sheets and the propylene glycol on the outer surface. Sheets added with 5% of hop β-acids significantly improved the inhibitory effects towards non-sporulated Gram-positive bacteria (Listeria monocytogenes and Staphylococcus aureus). The developed sheets were then tested concerning their biodegradability in soil, with Chapter Article 3 verifying the effects of the hop extract incorporation into the polymeric matrix. The results revealed that hop β-acids incorporation into the polymeric matrix did not reduce the degradation process but limited the bulk hydrolysis, probably due to the lower diffusion of water molecules among the polymer chains. Thus, in the active sheets, the degradation occurred mainly through surface erosion. The study conducted in Chapter Article 4, on the other hand, investigated the inclusion complexation of the commercial β-acids rich hop extract with two distinct cyclodextrins, β-cyclodextrin (βCD) and 2-hydroxypropyl-β- cyclodextrin (HPβCD) and the evaluation of the obtained inclusion complexes (IC). The inclusion complexation enhanced β-acids thermal and oxidative stability and both IC presented great application prospects. Despite the lower stability evidenced by βCD-based IC in comparison with the IC prepared with HPβCD, possibly due to a higher content of β-acids on the molecule’s outer face, it exhibited faster release into meat products simulant solution, along with a higher antibacterial activity. Finally, the study presented in Chapter Article 5 investigated the individual incorporation (20% w/w) of the IC previously studied into PLA films. IC-added films were evaluated concerning their performance (mechanical, thermal, and morphological features), along with their in vitro (antioxidant, antimicrobial, quorum quenching, and antibiofilm properties) and in situ (test with a bologna real food system) bioactivity. This work confirmed the potential of inclusion complexation with cyclodextrins as carriers for hop β-acids and application in active packaging development. In situ results corroborated with the in vitro findings and indicated a possible extension of the lag phase in the natural microbiota of bologna and for L. monocytogenes intentionally inoculated. Overall, the studies herein presented are a good asset for the biopolymeric active packaging development, also reinforcing the potentiality of hop β-acids’ application. Keywords: Sustainability; Biopolymers; Natural bioactives; Cyclodextrins; Quorum sensing; Biofilm; Food preservation.